The Effect of Workload on Burnout in Employees of PT Bank XYZ - Naswa Bunga Octavia; Rahmawati Prihastuty (Journal of Social and Industrial Psychology, 2024)
The phenomenon of burnout is very commonly experienced by employees in the banking sector. Burnout is a state of individuals who experience physical or mental fatigue caused by excessive activity pressure. The purpose of this study was to determine whether there is an influence between workload on burnout in banking employees. This study uses quantitative research, with a research sample of 75 employees of PT Bank XYZ branch office. Data collection using a Likert scale consisting of the Burnout Assessment Tool (BAT) scale and the Quantitative Workload Inventory (QWI). The results revealed that the burnout experienced by employees was in the high category, namely 34.7%, then the workload received by employees was also in the high category, namely 44%. The regression test results show that there is a positive influence between workload and burnout with a coefficient value of 47.6%. So that the greater the workload received by employees, the greater the possibility of employees experiencing burnout.